Perlindungan Hukum terhadap Hak Waris Anak yang Lahir dari Perkawinan Tidak Dicatatkan - Ni Luh Putu Ayu Lestari; Ni Luh Made Mahendrawati; I Ketut Sukadana (Warmadewa Press, 2021)
The validity of a marriage if carried out according to the laws of religion and their respective beliefs and recorded in accordance with the applicable laws and regulations, so as to obtain a deed as proof of a marriage. However, in many societies that do not register their marriages, the consequences will have an impact on children born; therefore there is a need for legal protection. The formulation of the problem in this study (1) how is the position of children born of marriage not recorded? (2) How is the legal protection of the inheritance rights of children born of marriage not recorded? This study aims to determine (1) the position of children born of marriage not listed, (2) legal protection of inheritance rights of children born to marriages not recorded. The method used is a type of normative legal research with a legal approach and a conceptual approach. Conclusions from the results of the study are the position of children born from unregistered marriages that are legal if they have fulfilled the requirements of their respective religions and beliefs, but the marriage does not have legal force and children born do not receive legal protection regarding their inheritance rights. The extramarital child will inherit if there is authentic evidence in the form of a birth certificate as legitimate written evidence.